DERMATOGLYPHICS PATTERN OF JAIN POPULATION OF WESTERN RAJASTHAN (Journal of Forensic Medicine & Toxicology, 2011)
Background: The importance of dermatoglyphics in comparative human population studies hardly needs emphasis, for the simple reason that dermatoglyphic traits are under genetic control. Besides, they are known to vary considerably owing to the fact that they are controlled by many additive genes. Material & Methods: The study reports on bilateral palm prints among 200 unrelated individuals (100 controls and 100 Jain). The parameter studied were TFRC (Total Finger Ridge Count), AFRC (Absolute Finger Ridge Count), Finger Tip Ridge patterns. Furuhata’s index was calculated and results obtained were compared for both groups using statistical tools. Result: The mean TFRC and atd angle was statistically significant in Jain population as compare to general population, while AFRC has not shown any statistical significance. Finger tip ridge pattern for each finger along with Furuhata’s index was also calculated and shown remarkable difference between two groups of population. Conclusion : In Jain community ulnar loops being present in more numbers than in general population. Reverse is true for whorls, which are more in general population than in Jains. These findings can be of immense help for medicolegal experts.
Keywords: Dermatoglyphics; TFRC; AFRC; Finger Tip Ridge patterns